The Impact of Social Assistance on The Community In Bendoroto Village, Munjungan Sub-District, Trenggalek District - Dedi Widiyanto; M. Agus Syukron; Lita Juniati (CV. Publikasi Indonesia, 2024)
This research aims to evaluate the impact of social assistance on the community in Bendaroto Village, Munjungan District, Trenggalek Regency. The focus of this research is to understand the type of social assistance received, the economic and social impacts felt by the community, and the problems faced during the implementation of the program, Such problems include administrative issues and inequities in disbursement that result in delays in aid disbursement, which reduces aid effectiveness and hampers financial planning. The research methods used include surveys and interviews. The survey results showed that the majority of respondents received direct cash assistance (BLT) and food assistance, with 60% reporting an increase in purchasing power and 45% experiencing an increase in food consumption. Significant social impacts were also seen from the reduction of financial burden for 70% of respondents and the increase in productive motivation for 50% of respondents. However, significant problems were also identified, such as uneven distribution of aid (55%), delays in distribution (60%), and lack of information regarding aid (45%). These findings show that although social assistance contributes positively to economic and social well-being, there are weaknesses in implementation that need to be improved. Recommendations to increase the effectiveness of social assistance include improvements in the distribution system, increased transparency, and better counseling on the use of assistance. This research provides important insights for the development of social assistance policies that are more effective and responsive to the needs of the community